In vitro and in vivo evaluation for immunomodulatory activity of methanol extract of Sphaeranthus indicus (Linn) - Sneha J Anarthe; E. Malavika; A. Pravalika; M. Ganga Raju (International Journal of Phytomedicine, 2015)
The aim of the present investigation is to evaluate the immunomodulatory activity for methanolic extract of Sphaeranthus indicus Linn. at different doses as 100, 200 and 400 mg/kg bd.wt. in healthy wistar albino rats. The assessment of immunomodulatory activity was evaluated for humoral immunity (antibody titre, plaque forming cell assay and quantitative haemolysis of SRBC) and cellular immunity (delayed type hypersensitivity, T- cell population and drug induced myelosuppression) with antigen challenge by sheep RBCs. Methanolic extract of Sphaeranthus indicus along with the antigen (sheep red blood cells) showed significant increase in the circulating antibody titer and the number of plaque forming cells (PFC) in the spleen at the dose of 100 mg/kg bd.wt. as compare to 200 and 400 mg/kg bd.wt. Methanolic extract of Sphaeranthus indicus also showed significant (p < 0.01) increase in the DTH response, restoration of histological parameters, increase in lymphocytes and rosettes formation in T-cell population at dose of 400 mg/kg bd.wt. as compare to 100 and 200 mg/kg bd.wt. The present investigation reveals that Sphaeranthus indicus can be used as immunomodulator for activation of both specific and non- specific immune responses.